Implementasi Algoritma Sequential Search pada Sistem Pelayanan Pasien Berbasis Web Di Klinik ZM - Hizqiya Heryanto; Robby Maududy (Jurnal Sains dan Teknologi (JSIT), 2026)
The rapid development of information technology has accelerated the digitalization of healthcare services. However, medical record management at Klinik ZM is still performed manually, causing patient data retrieval to take a relatively long time, increasing the risk of recording errors, and reducing service efficiency. These conditions indicate the need for a web-based patient service information system capable of managing medical records in an integrated manner and accelerating patient information retrieval. In addition, manual data management becomes less effective as the number of patients continues to increase, making it necessary to implement an information technology-based solution that can support more efficient healthcare services. This study aims to develop a web-based patient service information system at Klinik ZM by implementing the sequential search algorithm in the medical record search feature to improve the speed of patient data retrieval and support service efficiency. The proposed system is expected to assist administrators and healthcare personnel in managing patient data in a more structured, accurate, and easily accessible manner. This study employed the waterfall software development method, which consists of requirement analysis, system design, implementation, and testing. The sequential search algorithm was implemented in the medical record search feature by comparing the input keyword sequentially with each stored record until the desired data was found. Functional analysis was conducted using the black box testing method to verify that all system features operated according to the specified requirements. The developed system integrates patient management, medical records, follow-up schedules, and billing into a single web-based platform. The results show that the developed system successfully integrates patient management, medical records, follow-up schedules, and billing features into a single web-based platform. The implementation of the sequential search algorithm accurately retrieved medical record data and reduced the search time from approximately 5–7 minutes in the manual process to 3–6 seconds in the developed system. All testing scenarios were declared valid, indicating that the system improves the efficiency of patient data management, accelerates medical record retrieval, and supports more effective healthcare services at Klinik ZM. Therefore, the implementation of the sequential search algorithm provides a simple, easy-to-implement, and effective solution for improving medical record retrieval, enhancing healthcare service quality, and increasing operational efficiency at Klinik ZM.